SYTEMATIC LITERAURE REVIEW : PENERAPAN METODE ALGORITMA C4,5 UNTUK KLASIFIKASI - Srifani, Dewi; Nugroho, Bangkit Indarmawan; Santoso, Nugroho Adhi (Universitas PGRI Semarang, 2022)
Abstract—Data mining is extracting data in processing information with the aim of finding important patterns in piles of data. With data mining we can classify, predict, and make a decision. Classification is a way of grouping a data according to the characteristics of a data to be classified. In the process, the classification is divided into two, namely manually and with the help of technology. Manual classification is a classification carried out by humans without the help of technology, while classification with the help of technology has several algorithms, including C4.5, Naive Bayes, Fuzzy, and K-Nearest Neighbor. 5 for classification, a systematic approach is used in the form of a systematic literature review (SLR). SLR is defined as a process in which the identification, assessment, and interpretation of all available research evidence is carried out with the aim of answering a number of research questions